Analysis of quantitative sudomotor axon reflex test patterns in patients with complex regional pain syndrome diagnosed using the Budapest criteria. Issue 11 (November 2019) - Lee, Ho-Jin; Kim, Se Eun; Moon, Jee Youn; Shin, Je-Young; Kim, Yong-Chul
Abstract : Background: Although the quantitative sensory axon reflex test (QSART) is used to evaluate sudomotor dysfunction in the diagnosis of complex regional pain syndrome (CRPS), its validity remains controversial. This study investigated the diagnostic performance of the QSART for CRPS and assessed associations between results of the QSART and other clinical variables. Methods: We examined the electronic medical records of 196 consecutive patients who underwent the QSART with a suspected diagnosis of CRPS, during the period from January 2013 to December 2015. To assess the diagnostic performance of the QSART for CRPS based on the Budapest research criteria, we calculated sensitivity, specificity, positive likelihood ratio and negative likelihood ratio. Furthermore, we performed binary logistic regression analyses to investigate the relationships between QSART results and other clinical variables. Results: The sensitivity and specificity of the QSART for diagnosing CRPS were 67.6% and 40.6%, respectively. The OR for diagnosing CRPS using the QSART was not statistically significant (1.43; 95% CI 0.65 to 3.14; p=0.376), whereas it was for distinguishing CRPS types I and II (4.11; 95% CI 1.34 to 12.57; p=0.013). In multivariable analysis, there were no correlations between the results of the QSART and other variables, except hypertension (OR=0.34; 95% CI 0.13 to 0.91; p=0.032). Conclusion: The QSART showed low diagnostic value as a screening or a confirmatory test for CRPS according to the Budapest research criteria. CRPS type II was more likely than CRPS type I to result in abnormal QSART results.